2020
DOI: 10.1007/s00425-020-03476-1
|View full text |Cite
|
Sign up to set email alerts
|

GbMYBR1 from Ginkgo biloba represses phenylpropanoid biosynthesis and trichome development in Arabidopsis

Abstract: Main Conclusion GbMYBR1, a new type of R2R3-MYB repressor from Ginkgo biloba, displayed pleiotropic effects on plant growth, phenylpropanoid accumulation, by regulating multiple related genes at different levels. Abstract Ginkgo biloba is a typical gymnosperm that has been thriving on earth for millions of years. MYB transcription factors (TFs) play important roles in diverse processes in plants. However, the role of MYBs remains lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…Five cDNA fragments of the putative R2R3-MYB gene were isolated and identified in G. biloba , namely, GbMYBF10 , GbMYBF2 , GbMYBFL , and two GbMYBF1s . 254–256 The expression level of GbMYBF2 had a significant negative correlation with flavonoid content and the transcript levels of GbPAL , GbFLS , GbANS , and GbCHI , whereas the opposite was seen for GbMYBF1 and GbMYBF10 . The overexpression of GbMYBF2 in Arabidopsis significantly inhibited flavonoid accumulation, which reflected the repression of a large number of genes associated with flavonoid biosynthesis, including CHS , F3H , FLS , and ANS .…”
Section: Biosynthesis and Biotechnological Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Five cDNA fragments of the putative R2R3-MYB gene were isolated and identified in G. biloba , namely, GbMYBF10 , GbMYBF2 , GbMYBFL , and two GbMYBF1s . 254–256 The expression level of GbMYBF2 had a significant negative correlation with flavonoid content and the transcript levels of GbPAL , GbFLS , GbANS , and GbCHI , whereas the opposite was seen for GbMYBF1 and GbMYBF10 . The overexpression of GbMYBF2 in Arabidopsis significantly inhibited flavonoid accumulation, which reflected the repression of a large number of genes associated with flavonoid biosynthesis, including CHS , F3H , FLS , and ANS .…”
Section: Biosynthesis and Biotechnological Productionmentioning
confidence: 99%
“…All identified genes involved in ginkgo flavonoid biosynthesis are listed in Table 3. 235,241–245,248,250,252,254–256…”
Section: Biosynthesis and Biotechnological Productionmentioning
confidence: 99%
See 1 more Smart Citation
“… 36 For instance, GbMYBF2 and GbMYBR2 were reported to negatively regulate biosynthesis of flavonoid in G. biloba . 80 , 81 GbbHLH, GbTrihelix , and three GbERFs contributed to flavonoid biosynthesis by regulating the expression of structural genes in the flavonoid biosynthesis pathway. 82 In recent years, some studies found that TCPs may also be involved in flavonoid biosynthesis.…”
Section: Candidate Gbtcps Involved In Flavonoids B...mentioning
confidence: 99%
“…U39568) was used as an internal reference gene for the calculation of relative transcript levels. Primers used for genes from kudzu were listed in Supplementary Table 6, and primers for genes from Arabidopsis were the same as in our previous study (Su et al, 2020). Each reaction (20 µl) contained 1 µM each primer, 1 µl cDNA (1:10 diluted), 7 µl RNase-free H 2 O, and 10 µl PCR buffer of SYBR Real Master Mix.…”
Section: Cloning and Expression Of Candidate Genes In P Lobatamentioning
confidence: 99%